Evaluation of the Aswaja Annahdliyah Curriculum in Early Childhood Education of NU Muslimat - Yuliwati, Yuliwati; Hardiyanto, Lutfi; Romdanih, Romdanih (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study aims to evaluate the effectiveness of the Aswaja Annahdliyah curriculum in Early Childhood Education (PAUD) institutions under Muslimat NU in Jakarta, as part of efforts to improve educational policy. The research adopts a qualitative approach with a program evaluation design based on the CIPP model (Context, Input, Process, Product). Data were collected through observations, in-depth interviews, and document studies involving two principals of “A” accredited Muslimat NU PAUD institutions. Data analysis was conducted thematically using Atlas.ti software and validated through triangulation of techniques and sources. The findings indicate that the Aswaja Annahdliyah curriculum is in accordance with the fundamental needs of early childhood and community expectations, supported by a strong legal foundation and Islamic values. The curriculum makes a significant contribution to strengthening children’s character and religiosity. However, several weaknesses were identified, including limited innovation in learning, minimal technology integration, insufficient professional development for teachers, and suboptimal school-parent collaboration. In addition, the evaluation instruments for learning outcomes need to be strengthened to support more responsive program decision-making. This study recommends the development of a more adaptive curriculum, enhancement of teacher capacity through continuous training, and strengthening of cross-sector partnerships. The implications of this research are expected to serve as a reference for developing a more holistic and sustainable Islamic values-based PAUD curriculum policy.